Readiness Of Industry Revolution 4.0 (Ir4.0) Implementation In Asset Integrity Management (AIM) - Shahril Fitri, Mustapha (2021)
The current mega trend of IR4.0 revolution is the game changing technology for Malaysian business ecosystem. Enterprises of different scales are currently defining the implementation strategies for the inevitable transformation to IR4.0. As the manufacturing sector leading in the transformation process, the other sectors are slowly picking up the inevitable revolution inclusive of the building maintenance related services. Ensuring the integrity of assets and building through the adoption IR4.0 technologies is the pillar to a better building maintenance initiative however the needs of understanding the current state of affairs is crucial in narrowing the gap for the anticipated transformation. In this research, the study will gauge the readiness level of Malaysian’s Asset Integrity Management stakeholders in adopting IR4.0 by analyzing three key components i.e. people, technology and process. The objectives of this research are to identify the benchmarking methodology for the IR4.0 readiness level within asset integrity management and to analyse the readiness IR4.0 transformation of AIM within Malaysian building maintenance stakeholders The methodology of analysis will be adopted from proven model by established research institution within the country. The project looks at reviewing the current offering of IR4.0 technologies related to facilities management, identifying the methodology of benchmarking the IR4.0 readiness level within asset integrity management and analyse the IR4.0 transformation readiness level of Malaysian Facilities Management. A questionnaire survey was carried out and 111 out of 150 sets of questionnaires were collected from the targeted respondent to understand the readiness of IR4.0 implementation in Asset Integrity Management (AIM). A comprehensive analysis was carried out to further understand the data collected. It was found out, from the preliminary study, that the current level for Malaysian AIM in embracing the IR4.0 is barely a beginner.